Culture of peace with ICT - Nájar Sánchez, Olga; Universidad Pedagógica y Tecnológica de Colombia; Pedraza Córdoba, Juanita del Pilar; Universidad Carlos III de Madrid; Rodríguez Tamayo, Ilba Yanet; Universidad Pedagógica y Tecnológica de Colombia; Cuervo Gómez, William Oswaldo; Universidad Pedagógica y Tecnológica de Colombia; Ortiz Ortiz, Mary Luz; Universidad Pedagógica y Tecnológica de Colombia; Prieto González, Lynda Yohanna; Universidad Pedagógica y Tecnológica de Colombia; Carvajal Medina, María Patricia; Hinestroza Vélez, Juan Pablo; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2022)
This book is one of the results of the research project entitled Culture of Peace with ICT: improving school coexistence in the classroom, developed by the research group Educational Virtual Environments (AVE) of the Pedagogical and Technological University of Colombia, with the aim of to attend to oneof the many demands that are observed in educational institutions, in daily life, such as conflict resolution. Based on the main objective of the project, it was possible to have close knowledge of what happens in spaces, such as classrooms, in which a student can share daily and in which he is not alien to the confrontation of situations that motivate conflicts; The information collected made it possible to contribute to the development and strengthening of competencies and skills for the positive and peaceful management of those conflicts that underlie the referenced spaces. For this, three educational softwares were designed that helped students to interact and understand ways to solve some conflictsthat they live, especially, with their classmates. In the teaching field, those same software were the support for the work that they had to develop in compliance with Decree 1038 of 2015, which established the Chair of Peace as mandatory in all educational institutions in Colombia; These technological tools showed a different way of working the Chair of Peace and, at the same time, facilitated its learning, reflection and dialogue that the Decree itself deals with, on Culture of Peace, Education for Peace and Sustainable Development. Studies, such as the one presented in this book, show multiple achievements; Thus, in addition to the aforementioned, it is feasible to indicate that the implementation of the software facilitated the power to provide children with tools that would allow them to recognize the causes of their differences, theorigin of conflicts and the way to reach satisfactory solutions. The use of computer technologies, as an educational resource, allowed the transmission and appropriation of competences in a playful and natural way, among minors who are immersed in a knowledge society that requires the search fordifferent alternatives to face their daily events. In the chapter of the Chair of Peace: a right of citizens and a duty of public powers, one of the manifestations of the Culture of Peace is presented, which constitutes an experiential and practical concretion of it within a social environment of special relevance as it is, the school. In the next chapter, with ICT in school coexistence, it is revealed how mediating technological tools in school coexistence open a new window, with a learning opportunity and allow teachers and students to understand that pedagogical strategies with ICT are important resources that contribute to improve school coexistence,with the incorporation of educational software. Finally, the last chapter presents the Panorama of ICT in Colombia and its relationship with the Culture of Peace, a section that makes it possible to demonstrate, once again, that the reviewed experiences reveal, on the one hand, the need to develop skills in the appropriate use of ICT in the framework of the knowledge society and, on the other hand, the need to promote access to information, to build knowledge in a collaborative way that allows a positive influence on the development of the Chair of Peace, strengthening the Culture of Peace, through ICT in the educational process and, especially, to reduce conflict and generate respect for difference and peace.